Degradation of dichlorodiphenyl trichloroethane (DDT) by using nanoparticles of iron and iron/copper - Zin, May Thant (Animo Repository, 2016)
Dichlorodiphenyltrichloroethane (DDT), one of the persistant organic pollutants, was degraded by using nano-size zero valent iron (NZVI) and NZVI with Cu. The Box Behnken Design of Experiments was used to determine the effects of four factors: namely, initial DDT concentration (Co), metal loading, % Cu (M), and pH of test solution, on the degradation of DDT. Experiments were conducted at room temperature. The response was expressed as mg DDT degraded per g of metal particles. Among four factors, the metal loading and initial DDT concentration were the most significant. Increasing the initial DDT concentration increased the amount of DDT degraded per unit amount of metal particles. According to the effect of metal loading, only a small amount of metal particles is necessary to effect DDT degradation. The degradation of DDT was different with NZVI alone and bimetallic NZVI/Cu. However, only the addition of Cu up to 5% of the total metal loading improved DDT degradation significantly. DDT degradation was the most favorable at pH 3 and the least was pH 2. The mg DDT degraded per g metal particles could be modeled by the equation R = 7.60 + 2.63Co -4.2M + 1.21pH. The optimum DDT degradation condition was also observed. © 2016 - IOS Press and the authors. All rights reserved.